Developing mindsets for equity-focused continuous improvement: tracing shifts in an Ed.D. program using critical improvement science - Zumpe, Elizabeth; Uy, Phitsamay S.; Hakouz, Abeer; Szczesiul, Stacy Agee (Frontiers in Education, 2024)
Introduction: Two rising innovations in educational leadership development-using an equity lens and facilitating continuous improvement (CI)-depend upon leaders developing conducive mindsets for the work. However, little research has examined how educational leaders come to develop equityfocused CI mindsets. This is important given that countervailing habits of thinking are likely to develop within leaders' typical work environments. This paper traces the extent to which an Ed.D. program centered around a pedagogy of critical improvement science can foster shifts from typical habits of thinking towards equity-focused CI mindsets.Methods: Data consisted of 13 assignments and semi-structured interviews of six Ed.D. students participating in two parallel and interconnected courses during their first term. The two courses culminated in a common assessment: a White Paper about their equity-focused problem of practice and how their social identities shaped their understanding and role in addressing the problem. Through coding, analytic memos, and member checking, we traced patterns and shifts in students' thinking over time around five key domains of learning: problem identification, problem diagnosis, use of evidence, social identity, and equity leadership practices.We found emergent mindset shifts for all six participants across all learning domains. Students demonstrated new insights about problem analysis and becoming evidence-informed and user-centered, challenging their initial framing of problems through a systems approach to diagnosing problem. These insights intersected with new understandings of their social identities and practices as equity leaders as they reflected on more oppressed and privileged aspects of their identity and wrestled with new understandings that acting as equity leaders would entail disrupting power dynamics and empowering others for collective learning and action.The results reveal the potential of developing equity-focused CI mindsets through leadership programs that intentionally integrate methods of CI with critical analysis of one's social identity and leadership practices amid systems of oppression.